2009
DOI: 10.1161/circulationaha.108.821389
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Near-Infrared Fluorescence Molecular Imaging of Matrix Metalloproteinases in a Human Carotid Plaque Using a Matrix-Degrading Metalloproteinase–Sensitive Activatable Fluorescent Probe

Abstract: F ormation of unstable atherosclerotic plaque in the internal carotid artery carries a high risk for emboli and subsequent cerebral ischemic events. The fibrous cap of such a plaque may become thin and rupture as a result of the depletion of matrix components through the activation of proteolytic enzymes such as matrix-degrading proteinases. Enhanced matrix breakdown has been attributed primarily to a family of matrix-degrading metalloproteinases (MMPs) that are highly concentrated in atherosclerotic plaques b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 3 publications
1
35
0
Order By: Relevance
“…Through this imaging strategy, Van Fluorescence optical imaging can be used for a variety of molecular imaging applications in living subjects. Some specific examples include the study of matrix metalloproteinases activities using activatable imaging agents (35,447), detection of human epidermal growth factor receptor 2 (HER2/neu)-tumors in animal models using antibodies conjugated to rhodamine green (229), monitoring tumor growth and metastases using GFP-expressing tumors (161), and NIR activatable fluorescent imaging agents for imaging Alzheimer's disease that only "switch on" when bound to amyloid-beta (Abeta) protein (348).…”
Section: )mentioning
confidence: 99%
“…Through this imaging strategy, Van Fluorescence optical imaging can be used for a variety of molecular imaging applications in living subjects. Some specific examples include the study of matrix metalloproteinases activities using activatable imaging agents (35,447), detection of human epidermal growth factor receptor 2 (HER2/neu)-tumors in animal models using antibodies conjugated to rhodamine green (229), monitoring tumor growth and metastases using GFP-expressing tumors (161), and NIR activatable fluorescent imaging agents for imaging Alzheimer's disease that only "switch on" when bound to amyloid-beta (Abeta) protein (348).…”
Section: )mentioning
confidence: 99%
“…74 The first application of this technology was recently reported in carotid plaques examined ex vivo with a MMP-sensitive fluorescent probe, where hot spots corresponding to proteolytic activity of MMP-9 were identified at the origin of the internal carotid artery and at the level of the common carotid bulb. 75 …”
Section: Proteolysis and Plaque Imagingmentioning
confidence: 99%
“…These processes have become targets of various molecular imaging techniques, as they potentially allow non-invasive risk stratification of individual patients with carotid artery stenosis. 9,10 Recently, several studies have shown the feasibility of 18 F-sodium fluoride ( 18 F-NaF) positron emission tomography (PET) for imaging of atherosclerotic plaques. 11-13 18 F-NaF predominantly binds to areas of microcalcification within the plaque.…”
Section: Introductionmentioning
confidence: 99%